2007
DOI: 10.1111/j.1538-7836.2007.02696.x
|View full text |Cite
|
Sign up to set email alerts
|

MyosinIIa contractility is required for maintenance of platelet structure during spreading on collagen and contributes to thrombus stability

Abstract: Summary. Background: MyosinIIs are adenosine triphosphate-driven molecular motors that form part of a cellÕs contractile machinery. They are activated by phosphorylation of their light chains, by either activation of myosin light chain (MLC) kinase or inhibition of MLC phosphatase via Rho kinase (ROCK). MyosinIIa phosphorylation underlies platelet rounding and stress fiber formation. Objective: To identify the functional significance of myosinIIa in platelet spreading and thrombus formation on collagen using i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
64
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 35 publications
(62 reference statements)
8
64
0
Order By: Relevance
“…The observation that loss of aggregate stability in the presence of either Src kinase blockade or actin disruption is associated with retraction of lamellipodia and the appearance of single rounded platelets leads us to speculate that Src kinases contribute to aggregate stability through the actin cytoskeleton, especially bearing in mind the wealth of evidence for direct regulation of actin polymerization by integrin ␣IIb␤3 and GPVI. 8,16,17 Several group have reported stable thrombus formation at arteriolar rates of shear in vitro, as observed in the present study. 15,18,19 On the other hand, over the past few years, the use of various in vivo thrombosis models has revealed unstable aggregate formation in the absence of many platelet receptors or receptor mutants, including the ␣ 2A -adrenergic receptor, SLAM receptors, CD40L, and the diYF mutant of the integrin ␤3 subunit.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The observation that loss of aggregate stability in the presence of either Src kinase blockade or actin disruption is associated with retraction of lamellipodia and the appearance of single rounded platelets leads us to speculate that Src kinases contribute to aggregate stability through the actin cytoskeleton, especially bearing in mind the wealth of evidence for direct regulation of actin polymerization by integrin ␣IIb␤3 and GPVI. 8,16,17 Several group have reported stable thrombus formation at arteriolar rates of shear in vitro, as observed in the present study. 15,18,19 On the other hand, over the past few years, the use of various in vivo thrombosis models has revealed unstable aggregate formation in the absence of many platelet receptors or receptor mutants, including the ␣ 2A -adrenergic receptor, SLAM receptors, CD40L, and the diYF mutant of the integrin ␤3 subunit.…”
Section: Discussionsupporting
confidence: 77%
“…7 Further, inhibition of stress fiber formation using selective inhibitors or myosin IIa-deficient mice leads to reduced aggregate formation on collagen at arteriolar shear. 8,9 Rac and myosin IIa also contribute to thrombus stability in vivo, although this may additionally reflect their role in clot retraction. 8 -10 Collagen signaling is maintained over several hours in platelets and is required for sustained lamellipodia formation in vitro.…”
mentioning
confidence: 99%
“…Considering these differences in traction forces, we conclude that the mechanism to generate traction forces may depend on the cell type, possibly involving fluid flows and cytoskeletal disassembly processes apart from the actomyosin mechanism. Interestingly, it has been found that myosin contractility is required for maintenance of platelet structure during spreading (Calaminus et al, 2007). Future experiments, investigating the role of actomyosin in platelets, could be performed by adding blebbistatin or the rho kinase inhibitor Y27632.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Nonetheless, Rho kinase appears to play an important role in platelet function, by promoting focal adhesion-like complexes 18 and actin stress fibers in spreading platelets. 22 Such structures may play a key role in regulating the adhesive function of platelets, as inhibition of Rho kinase undermines the stability of platelet-matrix and plateletplatelet interactions in a shear field, 23 leading to a major defect in thrombus growth. 22 Genetic abnormalities in myosin IIA (termed the MYH9 disorders) encompass several autosomal dominant disorders, including the May-Hegglin anomaly and Epstein, Sebastian, and Fechtner syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…22 Such structures may play a key role in regulating the adhesive function of platelets, as inhibition of Rho kinase undermines the stability of platelet-matrix and plateletplatelet interactions in a shear field, 23 leading to a major defect in thrombus growth. 22 Genetic abnormalities in myosin IIA (termed the MYH9 disorders) encompass several autosomal dominant disorders, including the May-Hegglin anomaly and Epstein, Sebastian, and Fechtner syndromes. 24,25 A hallmark feature of these disorders is the failure of platelets to undergo shape change following soluble agonist stimulation, whereas platelet aggregation remains intact.…”
Section: Introductionmentioning
confidence: 99%